Keep an eye on the pupil: developing countries under chemical attack - Al-Goshae, Husni; Al-Karewany, Mahdy; Bamosmoosh, Mohamed; Modesti, Pietro Amedeo (Springer Nature, 2009)
This case-based article discusses clinical signs of chemical exposure, particularly organophosphate poisoning, and highlights the public health risks of toxic pesticide exposure in developing countries.